Pengaruh Pemberian Bonus terhadap Kinerja Karyawan pada Koperasi Simpan Pinjam Balo’ Toraja - Rante, Elsa; Sambara, Kordiana; Rasinan, Djusniati (YASIN, 2025)
This study aims to examine the effect of bonus giving on employee performance in the Balo' Toraja savings and loan cooperative. The population in this study is employees who work at the Balo' Toraja Savings and Loan Cooperative. The number of samples in this study is 34 samples. Sampling was carried out by providing a written statement to the respondents to the employees of the Balo' Toraja Savings and Loan Cooperative. The data analysis used was the correlation coefficient, determination coefficient and T test. The results showed that the results obtained from the correlation coefficient of pearson product moment. The results were obtained that there was a relationship or correlation between variables X and Y, and the type of relationship between variables X and Y was quite influential with a value of 108. While the results obtained from the value of the Coefficient of Determination (r-Square) in the bonus endogenous variable is 0.307, this shows that all independent variables simultaneously have an influence of 30.7% on Performance (dependent/bound variable), the remaining 69.3% is influenced by other variables that were not tested in the study. So the conclusion that there is a significant influence between bonuses and performance on KSP BALO' TORAJA because Ho is rejected and Ha is accepted, in other words, bonuses have a significant influence on the performance of karayawan.